Extended North Atlantic Oscillation and Greenland Blocking Indices 1800–2020 from New Meteorological Reanalysis - Edward Hanna; Thomas E. Cropper; Richard J. Hall; Richard C. Cornes; Mariano Barriendos (Atmosphere, 2022)
Based on newly-available meteorological reanalysis, we compile and present extended seasonal series of the North Atlantic Oscillation (NAO) and Greenland Blocking indices spanning 1800–2020, which we analyse for evidence of significant trends. This represents a major backward extension of the previously available instrumental-/reanalysis-based Azores–Iceland and principal component-based NAO indices, and allows us to evaluate the potential effect of natural climate perturbations, especially the 1809 and 1815 major volcanic eruptions and ~1790s–1830 Dalton solar minimum, on North Atlantic atmospheric circulation. We find that winters 1809/10 and 1816/17 mark positive NAO peaks, relative to several years before and afterwards, which is in accordance with the theory of volcanic forcing of climate. However, there is little evidence of a summer NAO volcanic signature. Overall, based on the significantly longer new reanalysis time series, the new series presented here corroborate and extend our previous results of: (1) a significantly more variable year-to-year NAO with a recent exceptional clustering of extreme events since 2000 for winter; (2) a significant increasing trend in blocking over Greenland in summer. These trends have major repercussions for the probability of the occurrence of extreme weather events over northwest Europe and for the sensitivity and response of the Greenland Ice Sheet to global warming, especially if they continue as an integral part of anthropogenic climate change.